2019
DOI: 10.1182/blood-2019-125894
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Derived CD19 CAR Cytokine Induced Killer (CIK) Cells Engineered with Sleeping Beauty Transposon for Relapsed B-Cell Acute Lymphoblastic Leukemia (B-ALL)

Abstract: Background Immunotherapy using patient-derived CAR T cells has achieved complete remission and durable response in highly refractory populations. However, logistical complexity and high costs of manufacturing autologous viral products limit CAR T cell availability. Allogeneic Cytokine Induced Killer (CIK) cells, a T-cell population characterized by the enrichment of CD3+CD56+ cells, have demonstrated a high profile of safety in acute lymphoblastic leukemia (ALL) patients (Introna M et al. Biol Blood Marrow Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Expansion was associated with clear observations of engrafted CAR T-cell functionality and persistent B cell aplasia in the absence of life-threatening toxicities. No evidence of GvHD was found in any of the treated patients and integration site analysis of the patients' peripheral blood confirmed the unique safety of this engineering approach in terms of genotoxicity [71]. Given that our findings are based on a limited number of patients and short-term follow-up, these results should therefore be interpreted as suggestive rather than definitive.…”
Section: Early Clinical Experiencesmentioning
confidence: 52%
See 1 more Smart Citation
“…Expansion was associated with clear observations of engrafted CAR T-cell functionality and persistent B cell aplasia in the absence of life-threatening toxicities. No evidence of GvHD was found in any of the treated patients and integration site analysis of the patients' peripheral blood confirmed the unique safety of this engineering approach in terms of genotoxicity [71]. Given that our findings are based on a limited number of patients and short-term follow-up, these results should therefore be interpreted as suggestive rather than definitive.…”
Section: Early Clinical Experiencesmentioning
confidence: 52%
“…All the GMP batches were released about 10 days after the end of production. These data demonstrate that our GMP platform is feasible and allows rapid and efficient expansion of highly potent CAR T-cells starting from easily available small amounts of PB [71].…”
Section: Qualitymentioning
confidence: 72%
“…Compared with viral transduction, the SB method showed a significantly higher genomic integration profile using minicircle (MC) and SB mRNA compared to lentiviral integration in CD19-CAR-T cells [ 222 ]. Lower costs and reduced regulatory demands offer clear advantages for production of non-viral vector-based cell therapeutics under GMP, and successful clinical application has already been reported for CD19-CAR-CIK cells [ 223 , 224 ]. Furthermore, a SB-engineered signaling lymphocytic activation molecule (SLAM) family member 7 (SLAMF7)-specific T cell product for treatment of patients suffering from multiple myeloma is currently under investigation in a phase I/II clinical trial CARAMBA-1 (NCT04499339; EU Horizon 2020 project).…”
Section: Cell Therapeutics: the Past The Present And The Futurementioning
confidence: 99%
“…Furthermore, a SB-engineered signaling lymphocytic activation molecule (SLAM) family member 7 (SLAMF7)-specific T cell product for treatment of patients suffering from multiple myeloma is currently under investigation in a phase I/II clinical trial CARAMBA-1 (NCT04499339; EU Horizon 2020 project). Additionally, CIK cells can be CAR-redirected through lentiviral and non-viral transposon system [ 224 ], and can exert relevant ADCC upon incubation with clinical-grade mAbs due to CD16 expression [ 225 , 226 ].…”
Section: Cell Therapeutics: the Past The Present And The Futurementioning
confidence: 99%
“…42 This clinical trial showed no significant side effects at doses of CD33‐CAR NK92 cells up to 5 × 10 9 per patient with a significant effect on minimal residual disease biomarkers. Magnani et al conducted a phase I/II trial of therapy using Sleeping Beauty‐engineered allogeneic donor‐derived CD19‐CAR CIK cells for relapsed B‐cell ALL patients 43 . Four pediatric and seven adult patients received a single dose of CD19‐CAR CIK cells that contained mostly CD3 + cells (47.1% CD56 + cells).…”
Section: Car‐nk Cell Therapy In Clinical Trailsmentioning
confidence: 99%